AMBIVALENSI RADIKALISME AGAMA DALAM PERSPEKTIF MUHAMMADIYAH - Rohmadi Rohmadi (Universitas Muhammadiyah Ponorogo, 2018)
There is no sexiest word besides Radicalism. Its existence often makes people stricken with fear. Even those who guessed that the end of radicalism was a brutal act of terrorism. The end of the religion is related. Various types of prevention are carried out by various official governmental and private institutions. The aim is none other than so that the ideas that lead to acts of terror can be stopped. In understanding the meaning of radicalism, many are confused, because if it is traced, the equivalent of the word radicalism is not in accordance with the meaning. Because the meaning of the radik is root / rooted (meaning deep thinking / philosophizing), while people do too much, they may not necessarily think deeply. Meanwhile, the word ism itself which contains the meaning of a notion, should be distinguished by an act that ends brutally. Herein lies the error, the word used to describe this should be extremism. Because there are always people who overdo it.That the symptoms of radicalism among Muslims in the post-New Order era can be seen as an 'act of identity' carried out in order to respond and answer the crisis of identity they experienced in the midst of dramatic and dramatic changes that occurred in Indonesia in the early phase of transition to democracy. not right if always associated with religion. But it does not mean that in religion there is no action, in any religion there are always people who interpret religion in a textual way, raping the scriptures for their interests. So that short-sightedness leads to brutal action / terror. The Muhammadiyah which is the main guardian of the Unitary State of the Republic of Indonesia will also not agree with various kinds of violence, occupation and deviant acts. It's just that Muhammadiyah suggested that the handling that smelled of Islam be carried out with a persuasive approach. Therefore, if the government insists on repressive actions, new terrorists will emerge. The emergence of radicalism cannot be separated from the long history of this nation, herein lies the ambivalent nature that we must seek and solve together, so that such ideas do not reappear.